IMPACT OF FARM VIDEO PROGRAMMES ON THE KNOWLEDGE GAIN ON CASTOR CULTIVATION OF RURAL WOMEN - I. SREENIVASA RAO, R. NEELA RANI and (The Journal of Research, PJTSAU, 2017)
Video is one such tool which has not yet been fully exploited in the Indian educational system. Its ability to overcome limitation of a single subject has been widely recognized in the modern self learning systems of education. Thus, video can easily be used to transmit knowledge to farm women, even information can be updated as per requirement any number of times. A largemajority of the respondents (71.25%) had low level of knowledge with regard to castor cultivation before exposure to video programme and were in the category of medium level of knowledge (73.75%) on castor cultivation after exposure to video programme in experimental group. A majority of the respondents (60.00%) were in the category of low level knowledge with regard to castor cultivation before exposure and after exposure (not exposed) to video programme in control group. The study revealed that there was a significant difference of mean scores of knowledge gain between before exposure and after exposure to video programme in castor cultivation.